GAMBARAN PERSALINAN DENGAN SECTIO CAESAREA DI INSTALASI GAWAT DARURAT KEBIDANAN RUMAH SAKIT UMUM PUSAT SANGLAH DENPASAR TAHUN 2020 - Ni Luh Putu Juliathi; Gusti Ayu Marhaeni; Ni Made Dwi Mahayati (Poltekkes Kemenkes Denpasar, 2021)
Sectio Caesarea (SC) is a way to deliver a fetus. Sectio Caesarea is performed to prevent fetal and maternal death due to the dangers or complications that will occur if the mother gives birth vaginally. The Sanglah Central General Hospital Denpasar has a high rate of cesarean delivery with post-caesarean section mortality which tends to increase. The purpose of this study was to determine the description of childbirth with Sectio Caesarea in the Emergency Department of Sanglah Hospital Denpasar in 2020. This type of descriptive research uses a cross sectional approach. Implementation in April - May 2021 with the total sampling technique. The sample amounted to 554 people. Collecting data through registers and patient medical records. Data analysis using Univariate in the form of frequency distribution tables. The results showed that delivery by Caesarean section in the obstetrics emergency room of Sanglah Hospital Denpasar in 2020 mostly occurred at healthy reproductive age (76.17%), secondary education level (74.73%), multigravida pregnancy (61.9%) at term of gestation. (58.8%) single fetus (95.30%), malpresentation (45.2%) and severe preeclampsia (30.6%). Pregnant women are expected to know the risk factors for complications of pregnancy and childbirth, health workers are expected to be able to improve the ability to detect early complications of pregnancy and childbirth, further researchers can add other variables related to Caesarean section.